2015
DOI: 10.2486/indhealth.2014-0156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vehicle-ride exposure on cervical pathology: a meta-analysis

Abstract: Research to date on the effect vehicle-ride exposure has on the development of cervical pathologies in mounted Warfighters is conflicting. The purpose of this study was to determine if the literature suggests a definite effect of vehicle-ride exposure on cervical pathology. Databases were searched using multiple combinations of select terms. Twelve studies meeting the inclusion criteria were included in the meta-analysis. The results of the meta-analysis revealed that overall vehicle-ride exposure was likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These results further highlight the need for more actual vehicle and aircraft data to help us better understand the influence of vehicle exposure on spinal musculature fatigue and its relationship to injury. Future research into this area is especially important given reports 5,31,32 that have indicated cervical injury is of particular concern to pilots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results further highlight the need for more actual vehicle and aircraft data to help us better understand the influence of vehicle exposure on spinal musculature fatigue and its relationship to injury. Future research into this area is especially important given reports 5,31,32 that have indicated cervical injury is of particular concern to pilots.…”
Section: Discussionmentioning
confidence: 99%
“…5 The literature [33][34][35] suggested head-supported mass as a potential injury risk factor. One report 36 indicated that 74% of pilots who wore night-vision goggles experienced neck pain, compared with only 38% of helicopter pilots who did not wear the goggles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational exposure to whole‐body vibration (WBV) is experienced by drivers, 1,2 vehicle operators, 1,3 and off‐road machine operators 4‐6 . Among military personnel, sources of WBV include ground vehicles and aircraft 7‐10 . Although standards for limiting exposure to WBV have been in place for decades; there is a lack of understanding of WBV‐associated risks among safety and healthcare professionals 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, there are still many questions about the relationship between characteristics of the WBV exposure and adverse effects on the health of exposed workers. Studies (e.g., Bovenzi & Hulshof, ; Bovenzi et al, ; Burdorf & Hulshof, ; Chen et al, ; Kollock, Games, Wilson, & Sefton, ; Seidel, Hinza, Hofmannb, & Menzela, ; Tamrin, Yokoyama, Aziz, & Maeda, ; Viruet, Genaidy, Shell, Salem, & Karwowski, ; Wikström, Kjellberg, & Landström, ) concerning the identification of dose–response relationship are still trying to find a way to quantify these effects. Burström, Nilsson, and Wahlström () carried out a review about WBV and the risk of low back pain (LBP) and sciatica.…”
Section: Introductionmentioning
confidence: 99%